Reading, writing, speaking, and listening across the curriculum (Utah : The LPD Video Journal of Education, 2001)
Discusses the importance of the four communications skills: reading, writing, speaking, and listening. Also examines specific tactics and strategies for implementing curriculum mapping in order to improve literacy skills across the curriculum.
program 1. Every teacher a language teacher - program 2. putting the skills to work.
PTSL : Elementary edition (j.1), secondary edition (j.2)
Keywords: English language -- Rhetoric -- Study and teaching; Language arts; Interdisciplinary approach in education; Written communication